Determination of pesticide residues in peaches by using gas chromatography and mass spectrometric detection. Issue 14 (14th November 2019) - Samad, Abdul; Akhtar, Shazia; Shahid, Muhammad Munir; Ahad, Karam
ABSTRACT: A multi-residue method using selected ion monitoring mode GC-MSD has been developed for the quantitative analysis of 30 widely used pesticides in fresh peaches produced in Swat Malakand, Pakistan. The planned methodology involved a sample extraction procedure using liquid-liquid partition with acetonitrile followed by a clean-up step based on solid-phase extraction (SPE). Method validation was performed in accordance with European Union guidelines. The European Union criteria (recovery 70–120%, RSD <20%) were met for majority of pesticides. For most of the pesticides, signal-to-noise ratios were good and background-corrected mass spectra often contained sufficient diagnostic to enable identity and confirmation. The limits of quantification (LOQs) were in the range 0.01–1.0 mg/kg. The above method was successfully applied to the analysis of peach samples (n = 30) from the field. Pesticide concentration in real peach samples was compared with the maximum residue levels (MRLs). Pesticide residues were detected in 73% of the peach samples. Most frequent residues were metalaxyl, α-cypermethrin, azoxystrobin, dimethoate, tebuconazol, λ-cyhalothrin and spiromesifin in peach samples.